2019
DOI: 10.1021/acs.est.8b05833
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Urban-Use Pesticides and Management with Enhanced Stormwater Control Measures at the Watershed Scale

Abstract: Urban-use pesticides are of increasing concern as they are widely used and have been linked to toxicity of aquatic organisms. To assess the occurrence and treatment of these pesticides in stormwater runoff, an approach combining field sampling and watershed-scale modeling was employed. Stormwater samples were collected at four locations in the lower San Diego River watershed during a storm event and analyzed for fipronil, three of its degradation products, and eight pyrethroids. All 12 compounds were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…Water quality is impacted and often regulated at the watershed scale, so understanding and planning for management decisions within the entire watershed is more impactful than responding to water quality issues at a single site. Wolfand et al 104,105 and Gallo et al 111 concluded that the end watershed management goal greatly impacts the optimal spatial distribution, size, infiltrative properties, and performance needs of biofilters (Table 1). For example, concentration-based versus load-based standards should be approached differently; biochar-augmented non-infiltrating filters are recommended to meet concentration-based standards whereas load-based standards are best met with infiltrating conventional biofilters (Table 1).…”
Section: Discussion and Future Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Water quality is impacted and often regulated at the watershed scale, so understanding and planning for management decisions within the entire watershed is more impactful than responding to water quality issues at a single site. Wolfand et al 104,105 and Gallo et al 111 concluded that the end watershed management goal greatly impacts the optimal spatial distribution, size, infiltrative properties, and performance needs of biofilters (Table 1). For example, concentration-based versus load-based standards should be approached differently; biochar-augmented non-infiltrating filters are recommended to meet concentration-based standards whereas load-based standards are best met with infiltrating conventional biofilters (Table 1).…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…This result was even more exaggerated for fipronil, which is more hydrophilic and thus even more poorly removed by conventional biofilters (reduction of 93% with biochar compared to 55% for conventional). In the same case study, 105 in-river pesticide concentrations were more sensitive to biofilter performance than pesticide load, particularly when the biofilters were unable to infiltrate into the subsurface. In this case, installation of conventional biofilters throughout the watershed was unable to reduce concentrations to below concentration-based aquatic toxicity benchmarks.…”
Section: Watershed Scale Implementation Of Biochar-augmented Biofiltersmentioning
confidence: 91%
See 3 more Smart Citations